2014
DOI: 10.1093/rof/rfu030
|View full text |Cite
|
Sign up to set email alerts
|

Credit Markets with Ethical Banks and Motivated Borrowers

Abstract: This paper investigates banks' corporate social responsibility. The credit market is composed of two sectors: one for standard and one for ethical projects. Since ethical banks are committed to investing in ethical projects, standard and ethical banks compete in the market for ethical projects. The latter have also a social profitability, but a lower expected revenue with respect to standard ones. If their expected revenue is not too low, ethical projects are undertaken by motivated borrowers. The latter obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…The present results add multiple important reasons, such as "Shared Values" or "Rejection, disappointment and mistrust towards conventional banks and the financial system". While previous studies have expected social banks' placement of assets to be one of the main reasons for choosing social banks [7][8][9][10]22], the present results specify this general assumption by identifying at least seven dimensions (categories) of this reason, allowing for a much more specific investigation of customer preferences. Five reasons were identified as being of more potential relevance to depositor decision-making.…”
Section: Research Implicationssupporting
confidence: 51%
See 1 more Smart Citation
“…The present results add multiple important reasons, such as "Shared Values" or "Rejection, disappointment and mistrust towards conventional banks and the financial system". While previous studies have expected social banks' placement of assets to be one of the main reasons for choosing social banks [7][8][9][10]22], the present results specify this general assumption by identifying at least seven dimensions (categories) of this reason, allowing for a much more specific investigation of customer preferences. Five reasons were identified as being of more potential relevance to depositor decision-making.…”
Section: Research Implicationssupporting
confidence: 51%
“…One reason for this lack of evidence might be the remaining uncertainty about depositors' reasons for choosing social banks in general. Previous research has assumed that private customers hold deposits with social banks to give their money real meaning, to receive an extra stream of utility, and to reinforce their pro-social identity by financing social business projects [7][8][9]. However, Höhnke and Homölle [10] show that social banks' placement of assets alone cannot explain depositors' choice of social banks and argue that other reasons for choosing social banks must exist.…”
Section: Introductionmentioning
confidence: 99%
“…Since all four differences between social and conventional banks predominantly refer to social banks' investment selection, it is reasonable to expect that the investment selection is a key reason for depositors’ choice of social banks. Previous research has argued that private customers hold deposits with social banks to give their money real meaning, to receive an extra stream of utility, and to reinforce their pro‐social identity by financing pro‐social business projects (Barigozzi & Tedeschi, 2015; Cornée & Szafarz, 2014; Paulet et al., 2015). Depositors are even willing to receive lower interest rates on savings because their deposits are used to fund pro‐social businesses (Cowton, 2002; Cowton & Thompson, 2001; Cornée & Szafarz, 2014).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies have assumed that private customers hold deposits with social banks to give their money real meaning, to receive an extra stream of utility, and to reinforce their pro-social identity by financing pro-social business projects (Barigozzi & Tedeschi, 2015;Cornée & Szafarz, 2014;Paulet et al, 2015), implying that people hold deposits with social banks due to social banks' special placement of assets. San-Jose et al (2011) showed that social banks indeed differ from conventional banks in their placement of assets, meaning that social banks' investment selection creates additional value by financing pro-social or pro-environmental businesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation